Correlation of Body Weight and Spermatozoa Motility of Native Chickens with Feeding BSF Maggot - Andi Fausiah; Andi Tenri Bau Astuti Mahmud; Abdullah Umar (Chalaza Journal of Animal Husbandry, 2020)
This study was conducted to evaluate the reproductive potential of native chickens by examining the correlation between body weight and spermatozoa motility. The correlation analysis results obtained a correlation coefficient (r) of 0.475.  The results in this research was a significant value of 0.1960.05 means that statistically, there is a relationship between body weight and spermatozoa motility. Still, the correlation between body weight and spermatozoa is weak. Bodyweight gain is one parameter that can be used as a production standard. Based on the results studied, it can be concluded that there is a relationship with the correlation value between body weight and spermatozoa motility of male cocks with BSF Magot feeding.